Effects of an improvisation intervention on elite figure skaters` performance, self esteem, creativity, and mindfulness skills - Richard, V.; Halliwell, W.; Tenenbaum, G. (The Sport Psychologist, 2017)
The study examined the effect of an improvisation intervention on figure skating performance, self-esteem, creativity, and mindfulness skills. Nine elite figure skaters participated in a 10-session program based on Cirque du Soleil artistic principles. A mixed methodology using questionnaires, competition scores, and interviews was used to test the program effects on these variables. Descriptive statistics revealed small but imperative increases in competition performance, perceived artistic performance, self-esteem, creativity, and mindfulness. Significant (p < .05) effect of time was revealed only for creativity and artistic performance variables. Qualitative data supported these results. Skaters described verbally that movements were performed more freely, attention was better focused on performance, and they overcame shyness. Quantitative and qualitative data are discussed interactively in relation to performance enhancement and personal growth.